Dendrochemical analysis of Brachystegia longifolia Benth as an indicator of Sulphur deposition in a copper smelting area of Mufulira, Zambia - Charles Mulenga; Daigard Ricardo Ortega-Rodriguez; Hermes Dias Brito; Darius Phiri; Abubakar Sadiq Mohammed; Chisala A. Lwali; James H. Speer (Discover Applied Sciences)
Abstract High levels of Sulphur dioxide (SO2) emanating from a copper smelter in Mufulira, Zambia has been reported around the year 2000, exceeding environmental quality guidelines. This resulted in the overhauling and upgrading of an obsolete smelter, the principal source of pollution. However, there is limited environmental evidence on the comparative variations in SO2 emissions in Mufulira before and after the smelter upgrade. This study investigated the dendrochemical potential of Brachystegia longifolia in detecting environmental change induced by variations in industrial pollution load. B. longifolia wood discs were extracted at breast height, air-dried and sanded until the transverse surface and annual rings were clearly visible. µ-XRF spectrometer was used to determine the distribution of Sulphur by scanning and exposing samples along the bark-pith transverse surface to the X-ray beam, obtaining X-ray transmission intensity values of counts per second (cps) for Sulphur. Finally, the same radial slices were then scanned with a cellulose acetate calibration scale using an X-ray densitometry chamber. Digital images were then analysed with Windendro® program to determine wood density. The mean Sulphur distribution in tree rings at the beginning (2007) and completion (2014) of the smelter upgrades were 15.41 cps and 17.51 cps, respectively. By 2019, the highest Sulphur content in B. longifolia wood had significantly (p < 0.05) reduced to 13.28 cps. Furthermore, a significant reduction in wood density with increasing tree age was observed after the installation of the new smelter. 0.78 g/cm3 and 0.75 g/cm3 mean wood density were recorded in annual rings at the beginning and completion of the upgrades, respectively. However, the mean wood density had significantly (p < 0.05) reduced to 0.67 g/cm3 by 2019. The significant variations in the distribution of Sulphur and wood density in tree rings formed before and after upgrading an obsolete copper smelter demonstrates the dendrochemical potential of B. longifolia and possibly other Miombo woodland species, offering an opportunity to biomonitor the impact of industrial activities in the Miombo landscapes which are extensively distributed across sub-Saharan Africa.